PENGARUH EKUITAS MEREK DAN BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINUMAN ISOTONIK POCARI SWEAT DI SAMARINDA - Aditya Nugroho; Prof. Dr. Theresia Militina, SE, M.Si; Dr. H. Zainal Ilmi, SE, MBA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2019)
ABSTRACTThis research aims to find the effect of Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty and Promotion Mix Towards Buying Decision of Pocari Sweat Isotonic Drink in Samarinda            The sample of this research is unknown, thus the writer utilizes sampling technique with these following methods : Probability Sampling and                 Non-Probability Sampling, namely, Random Sampling and Accidental Sampling. With the approch from Hair, et. Al (2006), as much as 100 respondents and the analysis tool used is multiple linier regression with help from SPSS version 23.            Regression equation produced from the data processing and data analysis result is as follow :Y = - 1,1169 + - 0,012 X1 + 0,207 X2+ 0,264 X3 + 0,126 X4 + 0,673 X5            The Result shown that Brand Awareness, Brand Association, Perceived Quality, Brand Loyalty and Promotion Mix had significant effect towards Buying Decision. With R2  value on 0.692, Meant (69,2%) buying decision affected by      ( Y ) variable and the rest of (30,8%) is explained by other variable.            Based on the calculation result, it can be seen that Promotion Mix (58,5%) affected buying decision more than Brand Awareness (-0,8%), Brand Association (17,9%), Perceived Quality (25,8%), Brand Loyalty (9,6%)/